2009
DOI: 10.1557/proc-1193-259
|View full text |Cite
|
Sign up to set email alerts
|

XAFS of Pu and Hf LIII Edge in Lanthanide-Borosilicate Glass

Abstract: Lanthanide-Borosilicate (LaBS) glass capable to dissolve up to ~10 wt.% PuO 2 is designed for immobilization of plutonium-bearing wastes. The sample of LaBS glass with a target chemical composition (wt %): 9.0 SrO was prepared from PuO 2 powder and mechanically activated mixture of chemicals at 1500 C. The obtained product was visually homogeneous. Xray diffraction of the as-prepared glass showed that it mostly consists of a vitreous phase with small amounts of crystalline PuO 2 (or PuO 2 -HfO 2 solid solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…La atoms uniformly distributed in the glass structure without any clustering surrounded by about 6 nonbridging oxygen (O) atoms mixed with sodium (Na) and calcium (Ca) atoms to the impairment of the BO 4 groups. Additionally, because of their facile ionization behavior compared with those of lanthanides, various actinides (U, Pu, Np, Am, and Th) can be easily immobilized by conditioning borosilicate glasses. …”
Section: Types Of Waste Formsmentioning
confidence: 99%
“…La atoms uniformly distributed in the glass structure without any clustering surrounded by about 6 nonbridging oxygen (O) atoms mixed with sodium (Na) and calcium (Ca) atoms to the impairment of the BO 4 groups. Additionally, because of their facile ionization behavior compared with those of lanthanides, various actinides (U, Pu, Np, Am, and Th) can be easily immobilized by conditioning borosilicate glasses. …”
Section: Types Of Waste Formsmentioning
confidence: 99%
“…Glass melts were made with a SB2/SB3 Slurry Mix Evaporator (SME) a simulant and SB6 SME simulant both using hafnium oxide as a PuO 2 surrogate. Testing has shown that HfO 2 is the best surrogate for PuO 2 in glasses from solubility and glass structure perspectives (Lopez, 2003;Shiryaev, 2009). The SB2/SB3 simulant was on hand and available for initial testing.…”
Section: Surrogate Glass Fabricationmentioning
confidence: 99%